On stoichiometry and intermixing at the spinel/perovskite interface in CoFe2O4/BaTiO3 thin films. Issue 1 (18th November 2014) - Tileli, Vasiliki; Duchamp, Martial; Axelsson, Anna-Karin; Valant, Matjaz; Dunin-Borkowski, Rafal E.; Alford, Neil McN.
Abstract : The performance of complex oxide heterostructures depends primarily on the interfacial coupling of the two component structures. Here, we report on the chemical complexity of the heteroepitaxy between CoFe2 O4 and BaTiO3 on the atomic level. Abstract : The performance of complex oxide heterostructures depends primarily on the interfacial coupling of the two component structures. This interface character inherently varies with the synthesis method and conditions used since even small composition variations can alter the electronic, ferroelectric, or magnetic functional properties of the system. The focus of this article is placed on the interface character of a pulsed laser deposited CoFe2 O4 /BaTiO3 thin film. Using a range of state-of-the-art transmission electron microscopy methodologies, the roles of substrate morphology, interface stoichiometry, and cation intermixing are determined on the atomic level. The results reveal a surprisingly uneven BaTiO3 substrate surface formed after the film deposition and Fe atom incorporation in the top few monolayers inside the unit cell of the BaTiO3 crystal. Towards the CoFe2 O4 side, a disordered region extending several nanometers from the interface was revealed and both Ba and Ti from the substrate were found to diffuse into the spinel layer. The analysis also shows that within this somehow incompatible composite interface, a different phase is formed corresponding to the compound Ba2 Fe3 Ti5 O15, which belongs to the ilmenite crystal structure of FeTiO3 type. The results suggest a chemical activity between these two oxides, which could lead to the synthesis of complex engineered interfaces.